The effect of grain orientation on the morphological stability of the organic–inorganic perovskite films under elevated temperature *Project supported by the Youth Innovation Promotion Association of CAS (No. 2015167). (January 2017) - Wang, Dong; Chang, Yue; Pang, Shuping; Cui, Guanglei
Abstract: The fast developing perovskite solar cells shows high efficiency and low cost. However, the stability problem restricts perovskite from commercial use. In this work, we have studied the effect of grain orientation on the morphological stability of perovskite thin films. By tuning the inorganic/organic ratio in the precursor solution, perovskite thin films with both high crystallinity and good morphological stability have been fabricated. The thermal stability of perovskite solar cells based on the optimized films has been tested. The device performance shows no degradation after annealing at 100 °C for 5 h in air. This finding provides general guidelines for the development of thermally stable perovskite solar cells.